PENGEMBANGAN USAHA BAJU RENANG MUSLIMAH - Eva Latifah Eva Latifah (LPPM STIA Banten, 2016)
The development of micro, small and medium enterprises (MSMEs) can be considered as a strategic force in accelerating regional development. The growth of MSMEs is increasing every year and this is of course a strength in itself in economic development. Micro, Small and Medium Enterprises whose existence cannot be denied are home industries, most of which are dominated by housewives. This includes home-based Muslim/Muslimah swimwear businesses. Small businesses which were initially for personal consumption, developed for local community consumption, and ultimately moved to foreign consumption. This of course has an impact on increasing labor absorption and community welfare in the region, especially in the surrounding environment. What is the best development so that this business can run better and be more effective for economic development? Improvements must be made both in terms of management, technical production, marketing and logistics. So that in the end this business can compete well with other large industries.